Drought-related parameters reveal better drought tolerance of transgenic plants overexpressing a soybean cytokinin dehydrogenase gene - Lan Xuan, Hoang Thi; Tien-Dung, Nguyen; Minh Thanh, Trinh Thi; Minh Thu, Phan; Ngoc Vy, Le; Phuong Thao, Nguyen (Vietnam Journal of Biotechnology, 2023)
Drought stress is one of the most detrimental abiotic stresses that has undeniably negative impacts on the growth and development of soybean plants. According to previous studies, cytokinin-related genes have been proposed to play vital roles in plant response and adaptation to drought stress. From a report, the soybean gene GmCKX13 encoding cytokinin oxidases/dehydrogenase was shown to be upregulated under drought condition. In this study, GmCKX13-overexpressing soybeans were used to evaluate the involvement of GmCKX13 in plant adaptation to water scarcity condition. According to the results, the introduction of GmCKX13 transgene conferred the transgenic plants enhanced drought tolerance capacity, which was featured with higher drought-tolerant index and better water retaining in the tissue under water deficit condition in comparison with the wild-type plants. Additionally, the transgenic soybean plants also showed lower level of intracellular hydrogen peroxide content, which was in agreement with the stronger activities of hydrogen peroxide-scavenging enzymes - catalase and peroxidase. These results indicate a promising application of GmCKX13 in enhancing antioxidant defense system against oxidative damage caused by drought stress in plants. Taken together, therefore, it is suggested that GmCKX13 may contribute to soybean adaptability to drought stress, which would result in crop yield improvement.